Psychological and pedagogical conditions for the formation of theoretical thinking in junior schoolchildren according to the system of developmental education D. B. Elkonina-V. V. Davydova (Pedagogy of Higher and Secondary Education, 2011)
I his article is devoted to the problem of exploration of the structure and process of forming the theoretical thinning in primary schools according to D. B. Elkonin – V. V. Davydov’s system of developing teaching.
Keywords: theoretical thinking; substantial abstractedness; substantial generalization and empiric thinking; reasonable and theoretic thinking